BUKU DIGITAL DAN PENGATURANNYA - Andina, Elga (Jurnal Aspirasi, 2011)
The development of telecommunication technology has enable people to bring the highest used of Internet. People can now access many new sources of information from the net. We can download book from the net and bring it home cheaply. The trend of digital book is soon covered Indonesia in the next five to ten years. This trend gives new way to define book. It is not only printed papers anymore, but also a digital work that can be read and even heard. The trend would also change the way book system works. Not to mention, people’s culture in macro. Digital product change the way people producing, reading, reasoning to buy a book and the means of transfer knowledge. Having the trend grows rapidly in every cities, Government must find way to control the system. Digital works is basically free of control, which can lead to various point of view, including the misuse of the product. As the Government need to protect citizen’s intellectual rights, at the same time must provide the easy way to access knowledge, the rule of book system must be considered carefully.